WORK-LIFE BALANCE DAN BEHAVIORAL FINANCE GENERASI Z: PERAN MODERASI FEAR OF MISSING OUT PADA PENGUNJUNG KAWASAN KULINER HANGGAR BIAK - Yuni Riskita Mangopo; Rizka Cintya Edwar; Lisa Gresti Sella Damanik; Xenia Irene Sandy Landjang (Program Magister Manajemen STIE Widya Wiwaha Yogyakarta, 2026)
This study aims to analyze the effect of Work-Life Balance on the Financial Behavior of Generation Z and to examine the moderating role of Fear of Missing Out (FOMO) among visitors to the Hanggar Biak Culinary Area. This study is considered important because the financial behavior of Generation Z is influenced not only by rational factors, but also by digital social dynamics and consumptive lifestyles that develop through social media. The study employed a quantitative approach using the Partial Least Squares Structural Equation Modeling (PLS-SEM) method. Data were collected through questionnaires distributed to Generation Z individuals who had engaged in consumption activities in the Hanggar Biak Culinary Area. The model was evaluated through outer model and inner model assessments, while hypothesis testing was conducted using the bootstrapping procedure. The results indicate that Work-Life Balance has a positive and significant effect on Financial Behavior. These findings suggest that an individual’s ability to maintain a balance between work and personal life contributes to more directed and responsible financial management behavior. Fear of Missing Out (FOMO) was also found to have a positive and significant effect on Financial Behavior, indicating that digital social pressure and the urge to follow trends influence the financial behavior of Generation Z. However, FOMO was not able to moderate the relationship between Work-Life Balance and Financial Behavior. This study provides an empirical perspective on the financial behavior of Generation Z within the context of culinary areas as emerging spaces of digital social consumption in the modern era.